Difference between revisions of "009B Sample Midterm 2, Problem 4"

From Math Wiki
Jump to navigation Jump to search
(Created page with "<span class="exam"> Evaluate the integral: ::<math>\int e^{-2x}\sin (2x)~dx</math> {| class="mw-collapsible mw-collapsed" style = "text-align:left;" !Foundations:   |...")
 
Line 7: Line 7:
 
!Foundations: &nbsp;  
 
!Foundations: &nbsp;  
 
|-
 
|-
|Review integration by parts
+
|Integration by parts tells us <math style="vertical-align: -15px">\int u~dv=uv-\int v~du.</math>
 +
|-
 +
|How would you integrate <math style="vertical-align: -15px">\int e^x\sin x~dx?</math>
 +
|-
 +
|
 +
::You could use integration by parts.
 +
|-
 +
|
 +
::Let <math style="vertical-align: -5px">u=\sin(x)</math> and <math style="vertical-align: 0px">dv=e^x~dx.</math> Then, <math style="vertical-align: -5px">du=\cos(x)~dx</math> and <math style="vertical-align: 0px">v=e^x.</math>
 +
|-
 +
|
 +
::Thus, <math style="vertical-align: -15px">\int e^x\sin x~dx\,=\,e^x\sin(x)-\int e^x\cos(x)~dx.</math>
 +
|-
 +
|
 +
::Now, we need to use integration by parts a second time.
 +
|-
 +
|
 +
::Let <math style="vertical-align: -5px">u=\cos(x)</math> and <math style="vertical-align: 0px">dv=e^x~dx.</math> Then, <math style="vertical-align: -5px">du=-\sin(x)~dx</math> and <math style="vertical-align: 0px">v=e^x.</math> So,
 +
|-
 +
|
 +
::<math>\begin{array}{rcl}
 +
\displaystyle{\int e^x\sin x~dx} & = & \displaystyle{e^x\sin(x)-(e^x\cos(x)-\int -e^x\sin(x)~dx}\\
 +
&&\\
 +
& = & \displaystyle{e^x(\sin(x)-\cos(x))-\int e^x\sin(x)~dx.}\\
 +
\end{array}</math>
 +
|-
 +
|
 +
::Notice, we are back where we started. So, adding the last term on the right hand side to the opposite side,
 +
|-
 +
|
 +
::we get <math style="vertical-align: -13px">2\int e^x\sin (x)~dx\,=\,e^x(\sin(x)-\cos(x)).</math>
 +
|-
 +
|
 +
::Hence, <math style="vertical-align: -15px">\int e^x\sin (x)~dx\,=\,\frac{e^x}{2}(\sin(x)-\cos(x))+C.</math>
 
|}
 
|}
  

Revision as of 14:18, 8 April 2016

Evaluate the integral:


Foundations:  
Integration by parts tells us
How would you integrate
You could use integration by parts.
Let and Then, and
Thus,
Now, we need to use integration by parts a second time.
Let and Then, and So,
Notice, we are back where we started. So, adding the last term on the right hand side to the opposite side,
we get
Hence,

Solution:

Step 1:  
We proceed using integration by parts. Let and . Then, and .
So, we get
   .
Step 2:  
Now, we need to use integration by parts again. Let and . Then, and .
So, we get
   .
Step 3:  
Notice that the integral on the right of the last equation in Step 2 is the same integral that we had at the beginning of the problem.
So, if we add the integral on the right to the other side of the equation, we get
    .
Now, we divide both sides by 2 to get
    .
Thus, the final answer is .
Final Answer:  
  

Return to Sample Exam